(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
This research aims to identify the extent of the obligation to disclose the accounting for risk activity for portfolio insurance company in general and risk insurance contracts, in particular, and the extent of its effect in reducing or reduction of the amount of risk premiums underwriting portfolio of the insurance company, and in the light of this, the search is based on the fundamental assumption reflects this relationship, and achieve the aim of the research was conducted to measure the level of disclosure through the comparative analysis in accordance with the requirements of the fourth international standard, accounting and rule Iraqi number (10) with what is available from the information in the financial reports of national to the insurance company, and the use of financial analysis index to measure the risk of the portfolio company’s size, Researchers also touched during this search to my part to ensure the concept and importance of accounting disclosure in the insurance company, and also touched on the concept of determining the nature of the risk and the size of the premiums in the underwriting portfolio. The study concluded that a number of conclusions concerning the practical side, the most important of a correlation and effect between the level of accounting disclosure and the size of the risk premium subscription portfolio of national insurance company relationship, depending on the conclusions of the research was to provide a set of recommendations to the company in question, and that is consistent with The reality of the study and its importance.